Attitude toward Business and Business Intention of ABM and STEM Students of Senior High School of Divine Word Colleges in Ilocos Region, Philippines: The Role of Education - Abun, Damianus; Magallanes, Theogenia; Encarnacion, Mary Joy; Ranay, Frelyn B.; Tacmo, Chester M.; Bello, Bryan T. (Technium Social Sciences Journal, 2021)
The purpose of this study was to determine the level of attitude of ABM and STEM students toward business and their business intention and to find out if there is a difference of attitude toward business and business intention of both strands (ABM and STEM). To establish the theories of the study, the literature was reviewed. The study used descriptive correlational research design and to gather the data, the validated questionnaires were used. The population of the study was grade XII ABM and STEM students of the Divine Word Colleges in the Ilocos Region. The study found that their attitude toward business and their business intention is high and based on Pearson r correlation, it was found that there is a significant correlation between attitude toward business and business intention and therefore, the hypothesis is accepted. However, based on the F-test which measures the difference between the attitude of ABM and STEM students’ attitude toward business and their business intention, the study found that there is no significant difference between both strands when it comes to their attitude toward business and their business intention